1999
DOI: 10.1007/s004649900949
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection for submucosally invasive colorectal cancer

Abstract: Preoperative endoscopic resection for colorectal submucosal cancer is feasible, provided the resection is complete. The indications for surgical treatment should be determined after pathologic examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…However, whether the requisite distance should be > 1, > 2, or > 3 mm or only a clear margin is still under debate (21,(25)(26)(27). In our analysis we found a 25 % rate of local wall disease and the margin status showed to be an independent risk factor for that, mostly in sessile lesions that are our main group, in agreement with earlier studies as Hassan et al pointed out (22,28,29). Polyp configuration, differentiation and margin status were also statistically relevant for wall disease.…”
Section: Discussionsupporting
confidence: 91%
“…However, whether the requisite distance should be > 1, > 2, or > 3 mm or only a clear margin is still under debate (21,(25)(26)(27). In our analysis we found a 25 % rate of local wall disease and the margin status showed to be an independent risk factor for that, mostly in sessile lesions that are our main group, in agreement with earlier studies as Hassan et al pointed out (22,28,29). Polyp configuration, differentiation and margin status were also statistically relevant for wall disease.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding endoscopic data, polyp site was clearly specified in 17 series, accounting for 1,461 polyps. 14,[20][21][22]24,26,27,29,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]39 In such studies, the rectum was involved in 19.6 percent of the cases, the left colon in 71 percent, and the right colon in the remaining 9.4 percent. Polyp morphology was available in 19 series, enrolling 1,145 polyps.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Death because of surgical complications, inferred from 28 studies, was reported in 8 (0.8 percent) of 951 operated patients. [12][13][14][15][16][17][18][19][20][21][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][42] …”
Section: Descriptive Analysismentioning
confidence: 99%
See 2 more Smart Citations